Injury surveillance in multi-sport events: the International Olympic Committee approach - Junge, A.; Engebretsen, L.; Alonso, J. M.; Renström, P.; Mountjoy, M.; Aubry, M.; Dvorak, J. (British Journal of Sports Medicine, 2008)
Background: The protection of athletes` health by preventing injuries is an important task for international sports federations. Standardised injury surveillance provides not only important epidemiological information, but also directions for injury prevention, and the opportunity for monitoring long-term changes in the frequency and circumstances of injury. Numerous studies have evaluated sports injuries during the season, but few have focused on injuries during major sport events such as World Championships, World Cups or the Olympic Games.